2004
DOI: 10.1046/j.1439-0418.2003.00808.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidences of non‐additive effects of multiple parasitoids on Diatraea saccharalis Fabr. (Lep., Crambidae) populations in sugarcane fields in Brazil

Abstract: Biological control is a relatively benign method of pest control. However, considerable debate exists over whether multiple natural enemies often interact to produce additive or non‐additive effects on their prey or host populations. Based on the large data set stored in the São João and Barra sugarcane mills (state of São Paulo, Brazil) regarding the programme of biological control of Diatraea saccharalis using the parasitoids Cotesia flavipes and tachinid flies, in the present study the author investigated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…However, differences in magnitude were found between species due to biological characteristics and preferences (Echeverri-Rubiano et al 2022); this requires further study. In general, pest injury exhibited by sugarcane varieties under field conditions are related to levels of resistance or susceptibility (White 1993, Echeverri-Rubiano et al 2017); however, as it has been found that the magnitude of pest injury can be affected by environmental conditions, such as a species complex overlapping in time or spatial distribution (Rossi 2004, Smith 2005). In addition, it is also important to determine whether external lesions are entrance or emergence holes (Bessin et al 1990b).…”
Section: Discussionmentioning
confidence: 99%
“…However, differences in magnitude were found between species due to biological characteristics and preferences (Echeverri-Rubiano et al 2022); this requires further study. In general, pest injury exhibited by sugarcane varieties under field conditions are related to levels of resistance or susceptibility (White 1993, Echeverri-Rubiano et al 2017); however, as it has been found that the magnitude of pest injury can be affected by environmental conditions, such as a species complex overlapping in time or spatial distribution (Rossi 2004, Smith 2005). In addition, it is also important to determine whether external lesions are entrance or emergence holes (Bessin et al 1990b).…”
Section: Discussionmentioning
confidence: 99%
“…At present, D. saccharalis is controlled either by introduction of transgenic cultivars of sugarcane ( Arencibia et al., 1997; Setamou et al., 2002) or by biological control by artificially introduced exotic parasitoid Cotesia flavipes ( Baker et al., 1992). Both methods have undesirable side‐effects on non‐target organisms ( Setamou et al., 2002; Rossi , 2004; Rossi and Fowler , 2004a,b). Implementation of efficient pheromone‐based monitoring system for D. saccharalis might help to minimize the harm.…”
Section: Discussionmentioning
confidence: 99%